1981
DOI: 10.1159/000176513
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Raw Green Gram <i>(Phaseolus aureus Roxb) </i>and Green Gram Trypsin Inhibitors on the Activity of Certain Protein Metabolism Enzymes in Rats

Abstract: The influence of a raw green gram (RGG) diet, an autoclaved green gram (AGG) diet and green gram trypsin inhibitors (GGTI) incorporated in AGG diet on urinary and blood urea and creatinine levels in rats was studied. The activities of certain liver enzymes of pathways associated with protein or amino acid metabolism were also studied. The levels of urea and creatinine in urine and blood were found to be significantly increased in rats fed the RGG and GGTI-incorporated AGG diets when compared to the animals fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…The increase or decrease in the urea and creatinine values during drug administration and drug withdrawal agrees with previous findings of Sathyamorthy et al (1981). They reported increase in serum urea and creatinine in rat.…”
Section: Discussionsupporting
confidence: 91%
“…The increase or decrease in the urea and creatinine values during drug administration and drug withdrawal agrees with previous findings of Sathyamorthy et al (1981). They reported increase in serum urea and creatinine in rat.…”
Section: Discussionsupporting
confidence: 91%
“…This indicates the enhanced activity of the enzymes of the urea cycle and hence the increased amino acid catabolism. Our earlier studies [5] showed similar effects when rats were fed raw green gram and green gram trypsin inhibitor. The amino acids, aspartate and glutamate, are used for urea biosynthesis.…”
Section: Discussionsupporting
confidence: 55%
“…The type of changes in protein catabolism in liver due to pancreatic hypersecretion is not known. The influence of raw legumes and trypsin inhibitors on the activity of some protein catabolism enzymes in rats [4,5] and chicks [4] has been reported. Increased levels of urea cycle enzymes, blood urea, creatinine as well as an elevated excretion of urinary urea and creatinine have been reported in animals fed raw legumes [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The trypsin inhibitory fraction of raw green gram was isolated by the method of Kakade et al [11] with slight modification, as illustrated in our previous publication [27].…”
Section: Biological Experiments With Rats Preparation Of Green Gram Tmentioning
confidence: 99%